2021
DOI: 10.1016/j.molp.2021.05.022
|View full text |Cite
|
Sign up to set email alerts
|

A natural variation of an SVP MADS-box transcription factor in Triticum petropavlovskyi leads to its ectopic expression and contributes to elongated glume

Abstract: Triticum petropavlovskyi, commonly known as Xinjiang rice wheat, is a unique hexaploidy wheat grown in the Xinjiang area. T. petropavlovskyi is marked by its elongated glume (Eg) trait, which is controlled by gene P1 pet located on chromosome 7A (Wang et al., 2002;Watanabe and Imamura, 2002). The origin of T. petropavlovskyi has been disputed. It is generally accepted that P1 pet was introduced from tetraploid polish wheat (T. polonicum) via a hybridization with hexaploid common wheat (T. aestivum) (Akond et a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Recently, multiple groups identified VRT-A2 as the causal gene for P1 (Adamski et al 2021;Liu et al 2021;Xiao et al 2021). We therefore compared the sequence of VRT-B2 (TraesCS7B02G080300) in five T. ispahanicum accessions to Chinese Spring (RefSeqv1.0).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, multiple groups identified VRT-A2 as the causal gene for P1 (Adamski et al 2021;Liu et al 2021;Xiao et al 2021). We therefore compared the sequence of VRT-B2 (TraesCS7B02G080300) in five T. ispahanicum accessions to Chinese Spring (RefSeqv1.0).…”
Section: Resultsmentioning
confidence: 99%
“…We identified three clades consistent with a monocot-specific triplication of StMADS11-like genes. Proteins from each clade have been shown to influence glume or lemma length when ectopically expressed in wheat (Adamski et al 2021;Liu et al 2021;Xiao et al 2021), maize (Han et al 2012;Wingen et al 2012), rice (Sentoku et al 2005), and barley (Trevaskis et al 2007). The biological function of previously characterized SVP/StMADS11-like protein in grasses, alongside the fine-mapping data, makes SVP-A1 a promising candidate gene for P2.…”
Section: Svp-a1 Is a Promising Candidate Gene For P2mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study suggested that the deletion/insertion variation in VRT-A2 intron 1 might also cause intron retention and, therefore, a frame-shift mutation (Chai et al, 2021). More interestingly, a sequence rearrangement identical to that of VRT-A2 has been detected in T. petropavlovskyi (also known as "Daosuimai" or rice-head wheat), a hexaploid wheat subspecies that also has elongated glumes (Liu et al, 2021;Xiao et al, 2021). Together, these studies support two major conclusions: (i) the activation of VRT-A2 facilitated the origin of T. polonicum as a unique species; and (ii) the long-glume trait of T. polonicum was likely inherited by T. petropavlovskyi through a genomic hybridization between T. polonicum and an unknown hexaploid landrace, enabling the formation of T. petropavlovskyi as a special subspecies of T. aestivum (Dixon and Boden, 2021;Xiao et al, 2021;Xu et al, 2021).…”
Section: Genetic Bases Of Wheat Species and Subspecies Formationmentioning
confidence: 99%
“…Notably, some species‐forming genes, for example VRT‐A2 and Tasg‐D1 , also affect the development of grains, illustrating their pleiotropic effects. Ectopic expression of VRT‐A2 in Polish wheat promotes grain elongation without affecting grain width, resulting in increased grain size and weight (Backhaus et al, 2021; Liu et al, 2021; Xiao et al, 2021). In contrast, gain‐of‐function of Tasg‐D1 in Indian dwarf wheat leads to small, round grains by repressing BR signaling, suggesting that Tasg‐D1 , in contrast to VRT‐A2 , restricts grain development (Cheng et al, 2020).…”
Section: Shaping Yield Traits: Tillers Spikes and Grainsmentioning
confidence: 99%